Effectiveness Of Online-Based Administrative Services In Ambon Ambon City Government - Fientje Palijama; In Hutuely (International Journal of Business, Technology and Organizational Behavior (IJBTOB), 2026)
Digital transformation in the government sector is a crucial strategy for improving the quality of public services. This study aims to analyze the effectiveness of online-based administrative services within the Ambon City Government. The study employed a descriptive qualitative approach, with data collection techniques including observation, interviews, and documentation. The informants consisted of civil servants and service users. The results indicate that online-based administrative services improve service time efficiency, procedural transparency, and ease of access. However, service effectiveness still faces challenges such as limited network infrastructure, low digital literacy among the public, and suboptimal service dissemination. This study recommends strengthening human resource capacity, improving technological infrastructure, and providing digital education to the public to improve the quality of electronic-based public services.